2023
DOI: 10.1039/d3bm00663h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nanomaterial-mediated bacterial molecular action and their applications in wound therapy

Wanfeng Wu,
Mengjiao Duan,
Shuxuan Shao
et al.

Abstract: Nanomaterials antibacterial mechanisms and main action targets were highlighted in detail. Then, products enabled by nanomaterials used in wound therapy were elaborated, providing a theoretical foundation for broader nanomedicine applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 167 publications
(227 reference statements)
0
0
0
Order By: Relevance
“…Nanoenzymes are diverse but most of them mediate catalytic reactions (mainly redox reactions) [205]. The redox-catalyzed activity of nanoenzymes generates a free radical storm that breaks the ROS balance, thus destroying the integrity of cell membranes, degrading a wide range of molecules, including nucleic acids, proteins, polysaccharides, and lipids, and destroying the morphology of bacteria, thereby killing MDR bacteria [206][207][208][209]. Yao et al [210] reported the use of pathogen-targeting bimetallic BiPt nanozymes exhibiting dual-enzymatic activities, including peroxidase-mimic and oxidase-mimic activities, for the nanocatalytic treatment of an MDR pathogen.…”
Section: Combination Antibiotics and Phagesmentioning
confidence: 99%
“…Nanoenzymes are diverse but most of them mediate catalytic reactions (mainly redox reactions) [205]. The redox-catalyzed activity of nanoenzymes generates a free radical storm that breaks the ROS balance, thus destroying the integrity of cell membranes, degrading a wide range of molecules, including nucleic acids, proteins, polysaccharides, and lipids, and destroying the morphology of bacteria, thereby killing MDR bacteria [206][207][208][209]. Yao et al [210] reported the use of pathogen-targeting bimetallic BiPt nanozymes exhibiting dual-enzymatic activities, including peroxidase-mimic and oxidase-mimic activities, for the nanocatalytic treatment of an MDR pathogen.…”
Section: Combination Antibiotics and Phagesmentioning
confidence: 99%